Religion and New Media (The Phenomena of New Media Influences on Religion in the Digital Era) - Tajuddin, Fatjri Nur; Rahman, Fatmawati A.; Satar, Muhammad (Jurnal Kajian Manajemen Dakwah, 2024)
At the present time, the media has a very important role as a fast messenger with a wide range. The more developed the world becomes more modern, the role is expanding. The influence of the media developed after the discovery of radio and television and the last appearance of the internet. Satellites as signal senders now transmit sound and image waves throughout the world, even to remote areas. In relation to religion, in general, the essence of media globality makes religious followers use it to spread the teachings of their religion. Moreover, because in principle that the prophet who receives the revelation has a role in spreading religion, spirituality and guiding humans. At the end, it raises the question that whether new media can be used to spread religious culture, just as media expertise in advertising various products or other things? Religion and Media, if explored further, on the one hand have the same thing in terms of seeking the truth. The difference is that religion claims to have found the truth, while the media does not say that. One of the media disciplines is to check and verify until they find the truth as close as possible, so that the truth is relative. While the truth for religion is absolute. Religion as a world community is a very important part. Especially for people who live in areas with a religious and spiritual population. Apart from the diversity of meanings from the belief in a religion or sect of a religion, but one thing that might be the same is interpreted by adherents of religion that religion is not only a social institution but also as a relationship between humans and their God